2019
DOI: 10.21037/atm.2019.11.17
|View full text |Cite
|
Sign up to set email alerts
|

The use of neutrophil lymphocyte ratio to predict complications post cardiac surgery

Abstract: Background: Cardiac surgery remains the gold standard treatment for select cohorts of patients with coronary artery and valvular heart diseases. It induces an acute systemic inflammatory response due to cardiopulmonary bypass (CPB), myocardial arrest, and surgical trauma. There is growing evidence that increased inflammation leads to greater complications and poorer outcomes for patients post cardiac surgery.Neutrophil/lymphocyte ratio (NLR) is a promising marker of inflammation. This study assessed if NLR cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…Recently, some markers composed of the ratios of white blood cell (WBC) subgroups have been newly introduced and demonstrated to be associated with the risks and outcomes of cardiovascular diseases and related surgeries. For example, for cardiac surgery patients, the value of the neutrophil-to-lymphocyte ratio (NLR) can serve as a predictor of early and late mortality ( 4 , 5 ), postoperative acute kidney injury ( 6 ), and postoperative atrial fibrillation ( 7 , 8 ), while the platelet-to-lymphocyte ratio (PLR) has been reported to be a predictor of prognosis in patients with aortic dissection ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some markers composed of the ratios of white blood cell (WBC) subgroups have been newly introduced and demonstrated to be associated with the risks and outcomes of cardiovascular diseases and related surgeries. For example, for cardiac surgery patients, the value of the neutrophil-to-lymphocyte ratio (NLR) can serve as a predictor of early and late mortality ( 4 , 5 ), postoperative acute kidney injury ( 6 ), and postoperative atrial fibrillation ( 7 , 8 ), while the platelet-to-lymphocyte ratio (PLR) has been reported to be a predictor of prognosis in patients with aortic dissection ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the NLR is closely related to the prognosis of patients with tumors [9,10], and cardiovascular disease [11][12][13]. At present, studies have been conducted on NLR and speci c high-risk populations of AKI, such as emergency surgery [14], burn surgery [15], cardiac surgery [16], and sepsis patients [17]. However, the relationship between the preoperative NLR and AKI after non-cardiac surgery under general anaesthesia has been barely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been found that some indicators such as cystatin C (18), neutrophils (19), urinary uromodulin (20), α 1-antitrypsin (21) and urinary IL-18(22) can predict the occurrence of AKI, creatinine is still the gold standard. As a result, we have no recognized indicators to judge AKI in the early stage.…”
Section: Introductionmentioning
confidence: 99%